Computational Design Approach to Re-Establish the Urban Fabric of Mongla: A Perspective from Grasshopper - Azad, Sumaiya Binte (MIST International Journal of Science and Technology, 2022)
The Padma Multipurpose Bridge Project is the genesis of some subsequent projects in Bangladesh among which developing Mongla Port is one of the priority values. Since Mongla is an integral part of southern Bangladesh, the government has taken initiatives to integrate the port uses for neighboring countries. An agreement was signed (Intra Bangladesh, Butan, India, and Nepal (BBIN) Trade) for offering multi‐modal transit access to India and Port access to Nepal, Bhutan and Eastern India. The objective of this study is to establish a computational way to analyze the existing fabric and restore a potential optimized fabric. The methodology of this study includes developing a computational approach, collecting data from secondary sources, analyzing the data set and adjusting it to the identified existing urban fabric. In this paper, a new tool is introduced named ‘Physarealm’, based on the algorithm of Grasshopper and Rhinoceros. MIJST, Vol. 9(2), December 2021: 23-29